Research on the improvement of industrial practices of transport and logistics students: case study in Lithuania - Čižiūnienė, Kristina; Batarlienė, Nijolė (Transport, 2019)
The article examines the impact of human resource practices on future employees in the transport and logistics sector where logistics companies operate. It presents the impact of the organization and implementation of industrial practices on the preparation of young specialists in the transport and logistics sectors and self-actualization of students. A research was conducted revealing how each industrial practice is actually perceived and accepted by a trainee, the industrial practice supervisor of a school of higher education and persons responsible for industrial practices in companies at the organizational level. The article also presents the expert assessment method and calculations of the compatibility of expert opinions. The obtained research results allowed developing a hypothetical model for the organization and implementation of the industrial practice process, which lists conditions for organizing and implementing industrial practices and potential results associated with the improvement of competencies, self-actualization of young specialists and concordance with study results.